Graduate employment : does field of study matter? - Seilane, Mpumelelo (University of the Witwatersrand, Johannesburg, 2023)
Skills shortage with graduate unemployment at face value appear as a contradiction in terms. However, this is emblematic of the South African economy. Albeit that the South African government invests a tremendous amount of resources towards the massification of higher education a significant proportion of graduates cannot find success in the labour market. Chief amongst the reasons why the South African government has taken this human capital investment path is to address the economic outcomes engendered by the historical policies of racial exclusion. Preferential access towards higher education institutions for previously disadvantaged individuals has been used as the weapon to combat poverty and inequality. However, having unemployed graduates in an economy severely lacking skills to grow is counter to the objective of reducing social inequality. The literature is at odds with regards to the relevance the field of study a graduate comes from in determining the prospects of success of a graduate in the labour market. So, with the use of the Quarterly Labour Force Survey (QLFS) dataset spanning from the first quarter of 2015 to the last quarter of 2019, this article employs a multinomial logistic regression model to investigate the correlates of employment amongst graduates in South Africa. The results indicate that graduate unemployment is fundamentally structural and therefore the field of study that a graduate comes from matters.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Economics to the Faculty of Commerce, Law and Management, School of economics and finance, University of the Witwatersrand, Johannesburg, 2023
Keywords: Graduate unemployment; Skills shortage; South African government; Unemployment; Higher education institutions; UCTD; SDG-8: Decent work and economic growth; SDG-4: Quality education